La evaluación de los aprendizajes en la enseñanza clínica de la enfermería. - Tinajero-González, Rosa María (Universidad de Sonora, 2019)
This article discusses the ways of evaluation by the teaching staff in the field of clinical practice in nursing, and the teacher is the one who develops strategies of teaching - as needed basis, to guide students to make their own learning for development of a professional future. It aims to see in a general way the process of learning assessment in clinical practice that made teachers summarized in three categories: academic performance of students, evaluation of products (results of teaching), and search standardizable attributes or traits, these methods are adapted according to the clinical area where the student develops. It can be an excellent professional without being therefore an excellent teacher and therefore no longer be an excellent evaluator that considers three main causes of errors in the evaluation process: Insufficient information halo effect, or tendency to establish categories and stereotypes error generosity, giving them a preamble to a hazard assessment invalid and unreliable bringing consequences of psychological, physical and social environment for nursing students.